PROSES DAN TANTANGAN PERSETUJUAN IZIN EDAR ALAT KESEHATAN BARU DI INDONESIA: STUDI LITERATUR ATAS PERMENKES NO. 62 TAHUN 2017 DAN UU KESEHATAN 2023 - Gunawan Widjaja; Wagiman; Dyah Ersita Yustanti; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (Jurnal Kesehatan, 2025)
The approval process for new medical devices in Indonesia is a strategic step to ensure the safety, quality, and usefulness of products circulating in the community. This study aims to critically analyse the administrative and technical licensing process for medical devices based on Permenkes No. 62 of 2017 and the Health Law of 2023 through a literature review. Primary data were obtained from an in-depth review of regulations, policy documents, and other relevant research findings. The study findings indicate that although regulations and licensing governance have significantly improved with the support of an online system and stricter evaluation procedures, implementation on the ground still faces various challenges. Key challenges include inefficient bureaucracy, disruptions caused by technological adaptation, limitations in laboratories and human resources, and harmonisation of standards with global regulations. It was also found that businesses, particularly MSMEs in the medical device sector, still face obstacles in understanding and meeting administrative and technical requirements for marketing authorisation. This study recommends strengthening socialisation, training, and integration of the monitoring system to support the independence and resilience of national medical devices, while ensuring consumer protection and public safety as users of medical devices.